Empathic Love Therapy to Reduce Depression among Female Victims of Domestic Violence - Sustriana Saragih; Kwartarini Wahyu Yuniarti (Faculty of Psychology, Universitas Gadjah Mada, 2021)
Female victims of domestic violence often experience depression. This research used Empathic Love Therapy (ELT) to reduce depressive symptoms, by enabling individual to understand one-self deeper by realizing, understanding, accepting, and loving all aspects of the self, which is the early process of healing. This research is quasi-experiment research using a single group simple interrupted time series design. Five women aged 30-60 years old who experience depression, based on BDI (Beck Depression Inventory) score, participated in an eight-session therapy. Participants were recruited purposively based on theory-based or operational construct sampling. Data analysis combined quantitative and qualitative methods, of which Wilcoxon Signed Ranks Test was used for quantitative analysis, whereas qualitative analysis adopted a descriptive analysis. Quantitative findings significant difference in BDI score between before and after treatment (Z = -2.023 with p= 0.043<0.05). Qualitative findings showed that participants were able to find survival personality that emerged from past painful experiences and plays a role in the depression symptoms they are currently experiencing. With the power of love they find from God, they are able to accept themselves, and focus their lives on their potential and positive future plans. Therefore, it can be concluded that Empathic Love Therapy is effective to be used to reduce depressive symptoms.